Respuesta :

gmany

Answer:

y + 3 = 2(x + 3)

Step-by-step explanation:

The point-slope form of an equation of a line:

[tex]y-y_1=m(x+x_1)[/tex]

m - slope

The formula of a slope:

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

From the graph we have the points (-3, -3) and (0, 3).

Calculate the slope:

[tex]m=\dfrac{3-(-3)}{0-(-3)}=\dfrac{6}{3}=2[/tex]

Put the value of the slope and the coordinates of the point (-3, -3) to the equation of a line:

[tex]y-(-3)=2(x-(-3))\\\\y+3=2(x+3)[/tex]

[tex]y=2x+3[/tex]